2021
DOI: 10.3390/ijerph18063006
|View full text |Cite
|
Sign up to set email alerts
|

Improving Vegetable Safety in China: Does Co-Regulation Work?

Abstract: In the last decade, vegetable safety issues have received growing attention from both consumers and public authorities in China, as vegetable safety hazards pose a serious threat to public health. In 2017, the Industry & Trade Bureau in China implemented a “Market Renovation Program”. This program includes the renovation of wholesale and wet markets, the formal registration of all stallholders in these markets and the introduction of a rapid test for pesticides residues. We apply the co-regulation framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In recent years, as living standards have risen, there has been a growing pursuit of a better quality of life [1]. When it comes to fresh commodities like vegetables, people typically turn to fresh food superstores or vegetable markets for their purchases [2].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, as living standards have risen, there has been a growing pursuit of a better quality of life [1]. When it comes to fresh commodities like vegetables, people typically turn to fresh food superstores or vegetable markets for their purchases [2].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-residue pesticide analysis is one of the most important analytical technologies involved in the global food trade and food safety supervision . With the continuous growth of global trade and the use of new pesticides in food products, the number of pesticide residues being monitored in food commodities is constantly getting larger. Due to the costs incurred for monitoring, the prices of food products have also been influenced. Meanwhile, the additional analysis may reduce the shelf life of perishable foods, which will potentially affect their sales. , Therefore, a large-scale, standardized, automated, and analytical approach has been perused and become a development direction in multi-pesticide residue analysis. , Additionally, the fifth point explicitly in the Green Analytical Chemistry rules also calls for miniaturization and automation of methods .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers also found that large supermarket chains provided vegetables at a significantly higher safety level compared with small-scale grocery stores (Alita et al, 2020). Moreover, it was shown that upstream wholesalers have an impact on the food safety level as the vegetables provided by larger wholesale markets were found to be safer than from smaller ones (Alita et al, 2021) because the larger markets established closer coregulation schemes with the local government.…”
Section: Defining Safe Foodmentioning
confidence: 99%
“…This chapter is based on the paper published as: Alita, L.,Dries, L., & Oosterveer, P. (2021). Improving Vegetable Safety in China: Does Co-Regulation Work?.…”
mentioning
confidence: 99%